Māori first foods: a Māori centred approach to understanding infant complementary feeding practices within Māori whānau - Rapata H; Heath A-LM; Wall C; Taylor R; Te Morenga L (Taylor and Francis Group on behalf of the Royal Society of New Zealand, 2022)
This study sought to explore infant complementary feeding practices among Māori whānau and the extent to which they may be informed by traditional and culturally specific practices, knowledge, personal beliefs and values. This study also endeavoured to explore how these practices, values and beliefs may have changed across time and between generations. Māori-centred qualitative methods were used within a theoretical framework of Kaupapa Māori and socioecological theories. Semi-structured interviews were conducted and analysed using Braun & Clarke’s method of thematic analysis to uncover key themes and a new theory for understanding infant feeding among Māori whānau. The themes and theories identified through this project suggest that infant complementary feeding is believed to be a natural and instinctive process for Māori whānau, one that is undergoing a process of decolonisation across generations. These theories indicate that Te Ao Māori centred living, grounded in mātauranga Māori is integral to infant feeding values and practices within Māori whānau. It is also clear that many Māori parents desire more culturally relevant infant nutrition information and support. Our findings should inform future updates to infant complementary feeding guidelines within Aotearoa New Zealand, as well as developments in infant nutrition information and support.
(c) The Author/s 2021
Keywords: Infant; nutrition; Māori; complementary feeding; health